PERTUMBUHAN DAN KELULUSHIDUPAN BENIH IKAN PATIN (Pangasius hypopthalmus) DENGAN SISTEM RESIRKULASI MENGGUNAKAN FILTER YANG BERBEDA - Amanda, Shandy Patria; Tang, Usman M; ', Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted from 19 January to 15 February 2016, during 28 days in Technology Laboratory of Fisheries Faculty and Marine Sciences, University of Riau. The aim of the research was to investigate the effect of different filters on growth and survival rates of catfishlarvae(Pangasius hypopthalmus) with recirculation system. Fish larvae were rearedin aquarium in density of 1 fish per liter. The method used was experiment with 4 treatments and 3 replications. The treatments were P1 or control = without filter; P2 or K,P,I= gravel, sand, palm fiber ; P3 or Z,P,I = zeolit, sand, palm fiber; P4 or S,P,I = spon, sand, palm fiber. The best treatment was achieved by P3or Z,P,I with survival rate 99 %, absolute growth weight 0,90 g, absolute growth length 3,2 mm, daily growth rate 9,2418 %and the best quality parameters of water recorded during in the research period was achieved by Z,P,I :temperature 25-29 oC, pH 7,2, turbidity 1,39 NTU, dissolved oxygen (DO)6,36 mg/L, ammonia (NH3) 0,0554 mg/L, nitrit (NO2-)0,186 mg/L, nitrat (NO3-) 1,32 mg/L.Keywords : Pangasius hypopthalmus, Filter, Recirculation, Zeolit, larvae